ENDOLENFATİK KESE TÜMÖRÜ: OLGU BİLDİRİMİ - YILMAZLAR, Selçuk; ABAŞ, Faruk; ÖZTÜRK NAZLIOĞLU, Hülya; KORFALI, Ender (Cerrahpaşa Medical Journal, 2014)
Background.- Endolymphatic sac tumors are rare intracranial tumors originating from temporal bone of the endolymphatic sac. They are histologically nonaggressive lesions, but often become locally invasive. We report one patient with pathologically proven endolymphatic sac tumor. A 45-year-old woman admitted a 7-year history of progressive right-sided hearing loss and recent onset of localized right ear pain. Magnetic resonance imaging showed a solid, heterogeneous enhancing mass in the petrous portion of the temporal bone resembling glomus jugulare tumor. The patient underwent a combined presigmoid and retrosigmoid approach to the tumor and partially resected. Observations.- She remained neurologically stable and underwent gamma-knife radiosurgery for residual and recurrent tumor after follow-up of 9 months. It is indispensable to differentiate between endolymphatic sac tumors and other pathologies, since requires to a different surgical strategies. Endolymphatic sac tumor invades the petrous bone and surrounds the neurovascular structures extending intracranially. A complete radical resection without neurological deficits is impossible in advanced cases. The role of adjuvant therapy is controversial and open to development. Because of this case, we reviewed the literature on endolymphatic sac tumors in changing concept.